Economic vs Fractured Basement: A Case Study from North Sumatra Basin - Ignatius Primadi (Ikatan Ahli Geologi Indonesia, 2013)
North Sumatra basin developed during the Early Tertiary (Eocene-Oligocene) as a result of an oblique subduction of the Indian Oceanic Plate underneath the Sundaland continental block. The basin is comprised of Tertiary to Recent sediments that were deposited over Pre-Tertiary basement. Typically, in many places basement consists of complex igneous and metamorphic rocks, but it is different in the North Sumatra basin. Underneath this basin, there are carbonates (dolomites or limestones) and sandstones including the Eocene Tampur Formation that have been called economic basement. Economic basement refers to rocks that have no economic prospectivity whilst the formation is comprised of the sedimentary deposits. The term economic basement in the North Sumatra Basin should be reconsidered because some data shows porosity development in pores and fractures, therefore making them potential reservoir that can receive hydrocarbon charge from proven petroleum system in the basin.